Thomson scattering for x-ray generation through collision between laser and electron beams - Lubna Al - Sakal (College of Education for Pure Sciences, 2010)
Abstract The linear thomson scattering had been studied and optimum angle between the laser and electron beams obtained. The result show that for optimum value of Coff. pulse width and cross section area of interaction was obtained at an angle (α = 4.70 rad).